MEMBANDINGKAN REFORMASI PAJAK PENGHASILAN DI INDONESIA DAN SINGAPURA MENGGUNAKAN PENDEKATAN LUDER’S CONTINGENCY MODEL (ARIKEL INI TELAH DITARIK OLEH PENULISNYA) - Deddy Kurniawansyah (UNEJ e-Proceeding)
This study aimed to compare the tax reform in terms of income tax in Indonesia and Singapore, using Luder’s Contingency Model to determine the stimuli, providers and users of information, and implementation barriers. This study uses literatures which analyzed into Luder’s Contingency Model. We use secondary data obtained from web-based information on government financial institutions in both countries. The research suggests that there are differences between Indonesia and Singapore in tax reform in terms of income tax comprise change stimuli, implementation barriers and user or interested parties who support tax reform. Luder’s Contingency Model suggest that tax reform can succeed if given enough stimulus and minimize barriers to the implementation of tax reform. Tax revenue, tax ratio, investment climate and low level of public’s trust contribute to Indonesia’s tax reform. On the contrary, tax reform in Singapore is triggered by economic recession, willingness to increase the engagement of foreign investors and workload of tax authorities.